The impact of social dominance orientation on female entrepreneurial intention - Jeffrey Muldoon; Carol Lucy; Sheryl Lidzy (New England Journal of Entrepreneurship (NEJE), 2019)
Purpose Understanding the factors that influence entrepreneurs throughout the entrepreneurial process has been a vital topic of entrepreneurial research. Despite societal changes, male entrepreneurs still outnumber females. The purpose of this paper is to develop a greater grasp on the factors that contribute to this phenomenon. Design/methodology/approach Utilizing social dominance theory and social cognition theory, the authors suggest that a female entrepreneur's social dominance orientation (SDO) and mentorship experiences will influence her social and conventional entrepreneurial intention. Findings The authors' theorizing suggests SDO can lower entrepreneurial self-efficacy which in turn can lower conventional entrepreneurial intentions but increase social intentions in some women. However, if the entrepreneur has mentoring, the effect could be dissipated. Originality/value This paper is one of the first to examine the impact of SDO on entrepreneurial intentions, and builds on the work of other scholars.
Keywords: 650; Self-efficacy; Social dominance orientation